Traumatic double gastric rupture-a rare finding in blunt trauma abdomen - Barkesiya, BL; M, Kuldeep; Barolia, DK (International Journal of Medical Research and Review, 2015)
Road traffic accidents are increasingly common, in which blunt trauma abdomen is a common injury with solid organ and hollow viscus injury, but isolated gastric rupture is a rare injury. We report a case of isolated double gastric rupture in blunt trauma abdomen, which is very rare, caused by road traffic accident. Patient managed by immediate laparotomy and double layer closer of both anterior and posterior perforation.